Serotonergic activation during courtship and aggression in the brown anole, Anolis sagrei - Hartline, Jacob T. (PeerJ, 2017)
The role of serotonin (5-hydroxytryptamine, 5-HT) in social behavior regulation is not fully understood. While 5-HT release in nuclei of the social behavior network has generally been associated with inhibition of aggressive behavior across multiple classes of vertebrates, less is known about its effects on sexual, especially non-copulatory courtship display behaviors. Furthermore, most research has examined effects at 5-HT release sites, while studies examining the behavioral relevance of source cell populations have generated contradictory findings. This study utilized immunohistochemistry to examine the colocalization of 5-HT with Fos, an immediate early gene product and marker of neural activity, in the raphe and superior reticular nuclei of male brown anoles (Anolis sagrei) exposed to either aggression, courtship, or control social interactions. Supporting previous research, copulation was associated with a decrease in 5-HT activity, while a novel link between 5-HT activity and latency to non-copulatory courtship was also found. Within the aggression group, intensity and frequency of behavior were both associated with decreased 5-HT activity. An effect of social context was also seen, with anoles exposed to either courtship or aggression encounters showing decreased 5-HT activity in certain raphe and superior reticular nuclei populations compared to controls. Interestingly, context effects and behavioral effects were seen at separate brain nuclei, suggesting the presence of separate systems with distinct functional roles.